Methicillin-Resistant Staphylococcus aureus as a Probable Cause of Antibiotic-Associated Enterocolitis - Alison B. Lane; Nathanial K. Copeland; Fatma Onmus-Leone; James V. Lawler (Case Reports in Infectious Diseases)
Antibiotic-associated diarrhea is typically associated with Clostridium difficile. However, Staphylococcus aureus has also been described as a cause of antibiotic-associated enterocolitis and diarrhea and is likely an underrecognized etiology. We present a case of enterocolitis and urinary tract infection caused by methicillin-resistant S. aureus following antibiotic treatment.